The Role of Moderating Variables on BOLD fMRI Response During Semantic Verbal Fluency and Finger Tapping in Active and Educated Healthy Seniors - Rodríguez-Aranda, Claudia; Castro-Chavira, Susana A.; Espenes, Ragna; Barrios, Fernando A.; Waterloo, Knut; Vangberg, Torgil R. (Frontiers in Human Neuroscience, 2020)
Semantic verbal fluency is among the most employed tasks in cognitive aging research and substantial work is devoted to understanding the underlying mechanisms behind age-related differences at the neural and behavioral levels. The present investigation aimed to evaluate the role of moderating variables, such as age, sex, MMSE and proxies of cognitive reserve (CR) on the hemodynamic response evoked by semantic verbal fluency in healthy young and healthy older adults. So far, no study has been conducted to this end. To elucidate the exclusive effect of the mentioned variables on brain activation during semantic fluency, finger tapping was included as a control task. Results showed that disregarding adjustments for age, older adults displayed important parietal activations during semantic fluency as well as during finger-tapping. Specifically, the anterior intra-parietal sulcus and left inferior parietal lobule were areas activated in both tasks in the older group. Younger adults only displayed parietal activations related to age and sex when these demographics were employed as predictors. Concerning proxies of CR in semantic fluency, only vocabulary was an important moderator in both age groups. Higher vocabulary scores were associated with lesser activation in occipital areas. Education did not show significant correlations with brain activity during semantic fluency in any of the groups. However, both CR proxies were significantly correlated to brain activations of older adults during finger tapping. Specifically, vocabulary was associated to frontal regions, while education correlated with parietal lobe and cingulate gyrus. Finally, effects of MMSE were mostly observed on brain activation of older adults in both tasks. These findings demonstrate that the effects of moderating variables on shaping brain activation are intricate and not exclusive of complex verbal tasks. Thus, before adjusting for “nuisance variables”, their importance needs to be established. This is especially true for samples including older adults for whom a motor task may be a demanding operation due to normal age-related processes of dedifferentiation.